Neural networks applied to visual pattern recognition - a comparative study - Tadeusiewicz, Ryszard (1947- ); Mikrut, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we discuss the principles of using back-propagation neural networks for pattern recognition. The basic information on neural networks learning is presented. A comparison is drawn between classification performance of the back-propagation network and other pattern recognition methods. Special attention is paid to preprocessing of the required data. The following problems are discussed in detail: choosing network topology, selecting proper values for learning coefficients, and estimating the quality of learning and recognition processes.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka